2019
DOI: 10.3390/jcm9010056
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Overall Survival in Advanced Intrahepatic Cholangiocarcinoma Treated with Yttrium-90 Radioembolization

Abstract: Purpose: To evaluate factors associated with survival following transarterial 90Y (yttrium) radioembolization (TARE) in patients with advanced intrahepatic cholangiocarcinoma (ICC). Methods: This retrospective multicenter study analyzed the outcome of three tertiary care cancer centers in patients with advanced ICC following resin microsphere TARE. Patients were included either after failed previous anticancer therapy, including relapse after surgical resection, or for having a minimum of 25% of total liver vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 29 publications
3
28
0
2
Order By: Relevance
“…Our relatively [58] and Sangro et al [29]. Our study confirms previous findings that independent of indication, prognostic factors commonly associated with an increased survival rate are ECOG 0, reduced tumour burden, lack of cirrhosis and ascites, low number of chemotherapy lines prior to TARE and no extra-hepatic disease [16,57,[59][60][61][62]. Kurilova et al have shown that in mCRC patients in the salvage setting, 1-year OS can range from 10% to 90% based on independent baseline parameters (number of extra-hepatic disease sites, carcinoembryonic antigen, albumin, alanine aminotransferase level, tumour differentiation level and the sum of the two largest tumour diameters) [38].…”
Section: Discussionsupporting
confidence: 90%
“…Our relatively [58] and Sangro et al [29]. Our study confirms previous findings that independent of indication, prognostic factors commonly associated with an increased survival rate are ECOG 0, reduced tumour burden, lack of cirrhosis and ascites, low number of chemotherapy lines prior to TARE and no extra-hepatic disease [16,57,[59][60][61][62]. Kurilova et al have shown that in mCRC patients in the salvage setting, 1-year OS can range from 10% to 90% based on independent baseline parameters (number of extra-hepatic disease sites, carcinoembryonic antigen, albumin, alanine aminotransferase level, tumour differentiation level and the sum of the two largest tumour diameters) [38].…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, patients with CCA were again characterized by a long-lasting tumor stabilization and a survival of up to 3.7 years from first CS-PHP and a high ORR of 30.8%. Similarly, to CS-PHP, transarterial radioembolization (TARE) has been evaluated in small cohorts of patients with CCA in the second line and reached a promising 3-months response rate of 35% comparable to our results (Köhler et al 2019 ). Treatment with either TARE or CS-PHP has been discussed for each patient within a multidisciplinary tumor board including internal medicine, surgery, nuclear medicine, radiation oncology, pathology, and radiology, whereas TARE was most often not performed due to the lack of clear hypervascularization in pre-interventional imaging and risk for radiation-induced liver disease due to multiple lesions.…”
Section: Discussionsupporting
confidence: 86%
“…Many studies looked into the prognostic factors that predicted the survival outcomes in ICC. Various studies including the present study have shown extensive intrahepatic tumor burden and extrahepatic metastases to predict poor survival outcomes [18][19][20][21]. Most extrahepatic metastasis occurs in patients with advanced intrahepatic tumor stage [12].…”
Section: Discussionmentioning
confidence: 49%